The first complete genome sequence and pathogenicity characterization of fowl adenovirus serotype 2 with inclusion body hepatitis and hydropericardium in China - Xie, Zimin; Zhang, Junqin; Sun, Minhua; Zeng, Qinghang; Huang, Yunzhen; Dong, Jiawen; Li, Linlin; Huang, Shujian; Liao, Ming (Frontiers in Veterinary Science, 2022)
Since 2015, fowl adenovirus (FAdV) has been frequently reported worldwide, causing serious economic losses to the poultry industry. In this study, a FAdV-2, namely GX01, was isolated from liver samples of chickens with hepatitis and hydropericardium in Guangxi Province, China. The complete genome sequence of GX01 was determined about 43,663 base pairs (bp) with 53% G+C content. To our knowledge, this is the first FAdV-2 complete genome in China. There was a deleting fragment in ORF25 gene. Phylogenetic analysis based on the hexon loop-1 gene showed that GX01 is most closely related to FAdV-2 strain 685. Pathogenicity experiment of GX01 in 3-day-old and 10-day-old specific-pathogen-free chickens showed that although no mortality was observed within 21 days post infection (dpi), strain GX01 significantly inhibited weight gain of infected chickens. Moreover, FAdV-2 was still detectable in the anal swabs of infected chickens at 21 dpi. Necropsy analysis showed that the main lesions were observed in liver, heart, and spleen. Of note, hepatitis and hydropericardium were observed in the infected chickens. In addition, massive necrosis of lymphocyte was observed in spleen of infected 3-day-old chickens. We concluded that FAdV-2 strain GX01 is capable of causing hepatitis and hydropericardium, which will make serious impact on the growth of chickens. Our research lays a foundation to investigate the molecular epidemiology and etiology of FAdV.